Profiling circulating microRNAs in pregnancies complicated by type 1 diabetes, type 2 diabetes and gestational diabetes mellitus - Pheiffer, Carmen (University of Pretoria, 2022)
Dissertation (MSc (Reproductive Biology))--university of Pretoria, 2021.